The Repertoire of Traditional Malay Ensemble as a Source of Violin Practice Learning Material - Panji Suroso; Danny Ivanno Ritonga; Wiflihani Wiflihani; Mukhlis Mukhlis; Tri Danu Satria (BIRCU, 2020)
This study aims to examine in depth how the process of applying the Malay traditional music ensemble reportoar as a teaching material in practical learning to play violin instruments in unimed music education study programs in the odd semester 2020-2021.Based on the monitoring carried out by the lecturer team in the learning process to play the violin that has occurred so far, the practice of playing the violin is still being carried out with teaching material playing western classical music and playing popular music styles. This study was conducted using a qualitative approach, namely following the opinions of Miles and Huberman (1984), namely (1) data collection, which was carried out through interviews, document digest observation, recording and recording; (2) data reduction, which is done by summarizing, selecting the main things, focusing on the important things, looking for themes and patterns and removing unnecessary ones; (3) data display (data presentation), which is done by showing the data and presenting it in the form of narrative text and charts; (4) conclusion drawing / verification which is carried out by drawing conclusions and verifying the research findings. In this study, the findings suggest that: 1) The learning process carried out in learning the violin in this study is to apply the tiered learning method, starting from the preparatory level learning, basic learning, middle level learning, and advanced learning. 2). The introduction of the main principle in recognizing cengkok and grenek in violin playing is in the form of the jump tone technique. For example, a violin melody can be played 7 notes or 8 notes in one beat, but the melody interval steps vary between second, terts, quart, quint and so on. However, in a grenek melody, the intervals played are only in the form of a second up or a second down.